MENGELOLA ASET MEREK STRATEGIK: Studi empirik pada konsumen Kecap ABC di kota Ambon - Rainier Hendrik Sitaniapessy (Trunojoyo University of Madura, 2014)
This study stems from the decline in Top Brand Index from 2013 until thebeginning of the semester of 2014 for the category of soy sauce ABC brand .With thedecrease TBI requires the company to manage the brand as an asset to enhance brandloyalty can be achieved. A sample of 100 respondents were selected using purposivesampling technique was analyzed by using Partial Least Square, this research showingthat the company should be able to develop the confidence and satisfaction of its brandin order to be able to increase the loyalty of the brand in the eyes of consumers. Brandimage positive and significant impact on brand trust and brand satisfaction. BrandTrust have significant positive effect on satisfaction and brand layaly. But brand trustno significant effect on brand loyalty. Implications of research and future researchagenda developed